Reductive Nasal Profileplasty - Shadfar, Scott (Facial Plastic Surgery, 2019)
Reductive nasal profileplasty is often the pillar of aesthetic nasal surgery. The surgeon must be knowledgable in the key tenants of preoperative analysis and examination to better approach the core elements for hump takedown. Photo imaging or morphing is a practical and technically easy means to open the discussion with the patients to determine their specific goals and ensure that these goals align with their needs functionally. Various approaches can be taken dependent upon the demands from the patient's anatomy and surgical goals planned preoperatively. The component resection technique is described in detail, as well as discussions regarding the need to predict and prophylactically treat the possible long- and short-term sequelae that can occur with reductive nasal profileplasty. Complementary procedures should also be considered to achieve the most balanced nasal and facial aesthetic.
Keywords: rhinoplasty; dorsal hump; profileplasty; profile reduction